The Links between Cardiovascular Diseases and Alzheimer's Disease - Leszek, Jerzy; Mikhaylenko, Elizaveta V.; Belousov, Dmitrii M.; Koutsouraki, Efrosini; Szczechowiak, Katarzyna; Kobusiak-Prokopowicz, Małgorzata; Mysiak, Andrzej; Diniz, Breno S.; Somasundaram, Siva G.; Kirkland, Cecil E.; Aliev, Gjumrakch (Current Neuropharmacology, 2021)
The root cause of non-inherited Alzheimer’s disease (AD) remains unknown despite hundreds of research studies performed to attempt to solve this problem. Since proper prophylaxis remains the best strategy, many scientists have studied the risk factors that may affect AD development. There is robust evidence supporting the hypothesis that cardiovascular diseases (CVD) may contribute to AD progression, as the diseases often coexist. Therefore, a lack of well-defined diagnostic criteria makes studying the relationship between AD and CVD complicated. Additionally, inflammation accompanies the pathogenesis of AD and CVD, and is not only a consequence but also implicated as a significant contributor to the course of the diseases. Of note, Ц#144;#128;оЦ#149;4 is found to be one of the major risk factors affecting both the cardiovascular and nervous systems. According to genome wide association and epidemiological studies, numerous common risk factors have been associated with the development of AD-related pathology. Furthermore, the risk of developing AD and CVDs appears to be increased by a wide range of conditions and lifestyle factors: hypertension, dyslipidemia, hypercholesterolemia, hyperhomocysteinemia, gut/oral microbiota, physical activity, and diet. This review summarizes the literature and provides possible mechanistic links between CVDs and AD.
Keywords: neuroinflammation